Mitigation of greenhouse gas emissions from beef cattle production systems. (1st October 2020) - Samsonstuen, Stine; Åby, Bente A.; Crosson, Paul; Beauchemin, Karen A.; Aass, Laila
ABSTRACT: The whole-farm model HolosNorBeef was used to estimate the efficiency of GHG emission mitigation strategies in Norwegian beef cattle herds. Various mitigation scenarios, involving female reproductive performance (i.e. calf mortality rate and the number of calves produced per cow per year), production efficiency of young bulls for slaughter (i.e. age at slaughter and carcass weight), and supplementation of an inhibitor currently reported as promising for enteric methane (CH4 ) inhibition (3-nitrooxypropanol; 3-NOP) was investigated in herds of British and Continental breeds. Reducing calf mortality and increasing the number of produced calves per cow per year both reduced emission intensities by 3% across breeds. Continental breeds showed greater potential of reducing emission intensities due to increased carcass production. Combining mitigation options in a best case scenario reduced the total emissions by 11.7% across breeds. The emission intensities could be further reduced by 8.3% with the use of 3-NOP.